Procedural support of the right to participate in administrative proceedings - Karamyshev, Aliaksandr V. (Journal of the Belarusian State University. Law, 2026)
This article examines the legal and organisational aspects of improving administrative proceedings in the Republic of Belarus within the paradigm of the procedural principle of openness. Within this context, significant features and a range of problems are identified. Attention is focused on the practical means of ensuring the right of a participant in administrative proceedings to be heard on the circumstances of the adopted administrative act.